Impact of benevolent leadership on follower taking charge: Roles of work engagement and role-breadth self-efficacy. Issue 4 (25th September 2018) - Xu, Qin; Zhao, Yixuan; Xi, Meng; Zhao, Shuming
Abstract : Purpose: The topic of employees' taking charge behaviors has garnered increasing interest in both practical and academic fields. Leaders play a critical role in influencing followers' taking charge behaviors, yet few studies have explored the predicting role of benevolent leadership. Drawing from proactive motivation literature, this paper aims to investigate a moderated mediation model that examines work engagement as the mediator and role-breadth self-efficacy as the moderator in the relationship between benevolent leadership and taking charge. Design/methodology/approach: Matched data were collected from 297 followers and their group leaders in three subsidiaries of a large telecommunication company in China. The authors used hierarchical linear modeling to test the hypotheses. Findings: The results revealed that benevolent leadership was positively related to followers' work engagement and consequently their taking charge behaviors. Moreover, such moderated mediation relationship was stronger among followers who had low rather than high levels of role-breadth self-efficacy. Research limitations/implications: The primary contribution of this study is building a contingent model for the effect of benevolent leadership on follower taking charge and thereby extending the nomological networks of both benevolent leadership and taking charge literatures. Another contribution is that this research provides a new perspective to understand how leadership leads to followers' taking charge behaviors. Originality/value: This is the first study to investigate how and when benevolent leadership predicts follower taking charge.